Screw-Assisted Soft Tissue Stabilization - A Paradigm Shift in Flap Fixation: A Case Series With a 3 Months Follow-Up - Amirreza Moayer; Hoori Aslroosta; Solmaz Akbari (Wolters Kluwer Medknow Publications, 2018)
Background: The final step in oral surgeries, proper positioning of the soft tissue, is considered as a major determinant of the clinical outcome. Different suturing anchors suffer fundamental flaws when they are supposed to guarantee the adequate flap fixation. This study aimed at proposing "screw assistant soft tissue stabilization" (SASS) as an alternative method for the conventional suturing techniques. Materials and Methods: A total of seven teeth in six healthy patients underwent surgical crown-lengthening by apically positioned flap technique. Surgical miniscrews were utilized for flap stabilization instead of periosteal sutures that are conventionally designed for soft tissue apical positioning. The widths of keratinized gingiva (KG) and the distance between gingival margin and cemento-enamel junction (GM-CEJ) were measured at baseline and 3 months after surgery. Results: All areas healed uneventfully. A significant increase in GM-CEJ distance without a significant change in the widths of KG was observed. Conclusion: The SASS technique seems to be able to fixate the flaps predictably and efficiently in lateral, apical, or coronal directions. In comparison, with traditional suturing techniques, it donates more comfort to both surgeons and patients. The advantages are of paramount importance in areas with limited surgical access and loose alveolar mucosa.